A membrane‐protected micro‐solid‐phase extraction method based on molecular imprinting and its application to the determination of local anesthetics in cosmetics. Issue 14 (17th May 2022) - Jian, Pengli; Muhammad, Turghun; Wei, Aixia; Wu, Beibei; Zhou, Tiantian
Abstract : As local anesthetics that are illegally added to cosmetics are harmful to consumer health, it is necessary to establish an efficient method for detecting these substances. Herein, a molecularly imprinted polymer (bupivacaine) was prepared by bulk polymerization and packed into a hollow fiber for use as an extraction phase to fabricate a membrane‐protected micro‐solid‐phase extraction device. The optimal values of the influencing parameters for the microextraction process were as follows: a sample solution pH of 9.0, a loading and washing time of 2 h, and an elution time of 32 min. A gas chromatography‐mass spectrometry method was established for the determination of local anesthetics and coupled with the microextraction method to successfully detect local anesthetics in cosmetic samples. The calibration curve for the proposed method was linear in the range of 0.4–50 mg/L and showed a good correlation coefficient ( r 2 ). The limits of detection for local anesthetics were in the range of 0.01–0.71 mg/L. The molecularly imprinted polymer exhibited good imprinting and selectivity, the micro‐solid‐phase extraction device was simple and inexpensive and fabrication was reproducible. The combination of molecular imprinting technology, membrane separation, and micro‐solid‐phase extraction methods used in this study can potentially be applied to pretreat local anesthetics in cosmetic samples.